Promotion of malignant phenotype after disruption of the three-dimensional structure of cultured spheroids from colorectal cancer - Piulats, Jose M. (Oncotarget, 2018)
Individual and small clusters of cancer cells may detach from the edges of a main tumor and invade vessels, which can act as the origin of metastasis; however, the mechanism for this phenomenon is not well understood. Using cancer tissue-originated spheroids, we studied whether disturbing the 3D architecture of cancer spheroids can provoke the reformation process and progression of malignancy. We developed a mechanical disruption method to achieve homogenous disruption of the spheroids while maintaining cell–cell contact. After the disruption, 9 spheroid lines from 9 patient samples reformed within a few hours, and 3 of the 9 lines exhibited accelerated spheroid growth. Marker expression, spheroid forming capacity, and tumorigenesis indicated that stemness increased after spheroid disruption. In addition, the spheroid forming capacity increased in 6 of 11 spheroid lines. The disruption signature determined by gene expression profiling supported the incidence of remodeling and predicted the prognosis of patients with colorectal cancer. Furthermore, WNT and HER3 signaling were increased in the reformed spheroids, and suppression of these signaling pathways attenuated the increased proliferation and stemness after the disruption. Overall, the disruption and subsequent reformation of cancer spheroids promoted malignancy-related phenotypes through the activation of the WNT and ERBB pathways.